2008
DOI: 10.1121/1.2932888
|View full text |Cite
|
Sign up to set email alerts
|

HRTF modeling in due consideration variable torso reflections

Abstract: Head related transfer functions (HRTFs) describe the physical path from an acoustical source to the ears. It can be gained within the relation of two measurements. The first will give the reference sound pressure in the virtual middle of the head the second has to be done in both ears. In literature exhaustive investigations concerning the idealized location of the second position can be found. Beyond that measurements with various artificial heads and human-beings considering various source directions (azimut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Our evaluation of the effect of HATO in HRTFs supported findings of earlier studies regarding the comb-filter like nature of the shoulder reflection, which was found to be most prominent if sound source, shoulder, and ear are aligned [4], [6], [7]. Because observed deviations in ITDs and ILDs were below the threshold of audibility for the vast majority of HATOs and source positions, we suppose perceived differences to be mostly due to spectral deviations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our evaluation of the effect of HATO in HRTFs supported findings of earlier studies regarding the comb-filter like nature of the shoulder reflection, which was found to be most prominent if sound source, shoulder, and ear are aligned [4], [6], [7]. Because observed deviations in ITDs and ILDs were below the threshold of audibility for the vast majority of HATOs and source positions, we suppose perceived differences to be mostly due to spectral deviations.…”
Section: Discussionsupporting
confidence: 89%
“…From an analysis of HRTFs measured for various HATOs, Guldenschuh et al [7] found that the most prominent torso reflections occur when ear, shoulder, and source are approximately aligned, and the source elevation is within 20 • below the horizontal plane to 40 • above. The authors further hypothesized that effects caused by the torso should be audible at least for critical source positions.…”
Section: Introductionmentioning
confidence: 99%
“…These maps indicate that model WB uses filter 2 to extract ripples in the range from 0.3 to 4 kHz caused by shoulder and torso reflections [15]. One limitation of the datasets used in this study is that the dependence of shoulder reflections on head orientation [29] is not accounted for. Training the model on variable shoulder reflections might potentially lower the contribution of these cues.…”
Section: Model Wbmentioning
confidence: 99%
“…The torso can act as a shield or a reflector depending on the HATO and source directions, and shows noticeable influences on measured HRTFs [185,208]. Brinkmann et al [209] demonstrated the audible deviations of HRTFs measured with fixed and variable HATOs.…”
Section: Considerations and Trends In Hrtf Measurementsmentioning
confidence: 99%